2021
DOI: 10.3390/cancers13030500
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Novel 177Lu-Labeled PNA Probes for Affibody-Mediated PNA-Based Pretargeting

Abstract: Affibody-mediated PNA-based pretargeting is a promising approach to radionuclide therapy of HER2-expressing tumors. In this study, we test the hypothesis that shortening the PNA pretargeting probes would increase the tumor-to-kidney dose ratio. The primary probe ZHER2:342-SR-HP15 and the complementary secondary probes HP16, HP17, and HP18, containing 9, 12, and 15 nucleobases, respectively, and carrying a 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) chelator were designed, synthesized, chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 34 publications
2
43
0
1
Order By: Relevance
“…To further improve the radioactive uptake of molecular probes by tumors and reduce the radioactive retention of normal organs such as the kidneys, the research team further optimized the molecular probes in a series of studies in which they conducted comparative evaluations in vivo and in vitro . The results showed that the molecular probe [ 177 Lu]Lu-HP16, containing 9 nucleic acid bases, has the highest tumor/kidney uptake ratio and is a promising molecular probe for targeted therapy of HER2-positive ovarian cancer ( 121 123 ).…”
Section: Overview Of Radionuclide-labeled Her2 Affibody Molecular Probesmentioning
confidence: 99%
“…To further improve the radioactive uptake of molecular probes by tumors and reduce the radioactive retention of normal organs such as the kidneys, the research team further optimized the molecular probes in a series of studies in which they conducted comparative evaluations in vivo and in vitro . The results showed that the molecular probe [ 177 Lu]Lu-HP16, containing 9 nucleic acid bases, has the highest tumor/kidney uptake ratio and is a promising molecular probe for targeted therapy of HER2-positive ovarian cancer ( 121 123 ).…”
Section: Overview Of Radionuclide-labeled Her2 Affibody Molecular Probesmentioning
confidence: 99%
“…Furthermore, in clinical trials of the bsAb-hapten platform, immunogenicity of the pretargeting agents has been an issue when anti-inflammatory drugs are not used as part of the pretargeting scheme. The other two platforms that have been reported are based on streptavidin–biotin binding or oligonucleotide hybridization as the pretargeting interaction. The clinical viability of the streptavidin–biotin methodology is hindered by problems with immunogenicity and the need to use clearing agents. , Finally, the nucleotide hybridization driven pretargeting platform, studied only in preclinical models, has suffered from poor tumor uptake (%ID/g) when full-length antibodies are used for targeting. While full-length antibodies are currently the primary and most attractive targeting vectors for pretargeting, the nucleotide hybridization approach has shown encouraging results with affibody targeting vectors, suggesting they represent a potentially fruitful alternative. …”
mentioning
confidence: 99%
“…As an alternative to the use of PNA chimeras, PNAs may also be used as motifs for supramolecular recognition in pretargeting approaches. ,, A schematic representation can be found in Figure . Pretargeting approaches typically rely on either bioorthogonal click reactions in vitro or in vivo, such as the inverse electron-demand Diels–Alder (IEDDA) reaction between trans -cyclooctene and tetrazine, or on the supramolecular recognition of a host and a guest, such as the interaction between adamantane and cyclodextrin .…”
Section: Pretargeting Studies Using Pna-based Imaging Probesmentioning
confidence: 99%
“…This alleviates the need for developing endosomal escape strategies and allows one to focus on other challenges, like the overall biodistribution and excretion of unbound probes. Several authors already successfully demonstrated the use of such a strategy involving PNAs. , …”
Section: Pretargeting Studies Using Pna-based Imaging Probesmentioning
confidence: 99%